Mixed convection magnetic nanofluid flow past a rotating vertical porous cone - Wahid, N. S.; Md Arifin, N.; Khashi’ie, N. S.; Pop, I.; Bachok, N.; Hafidzuddin, M. E. Hafidz (Isfahan Univ technology, 2022)
Magnetic nanofluids (MNFs) have been the focus of extensive research nowadays owing to their potential usefulness as a transfer medium. This study is concerned with the boundary layer flow and heat transfer of MNF past a rotating vertical cone with the embedment of the porosity regime and mixed convection. The buoyancy opposing flow on the combined free and forced convection is being emphasized in this study to evaluate the behavior of the fluid within this region and predict the point of the boundary layer transition. The initial formulation of the model is simplified appropriately by employing the suitable similarity transformation. The package of bvp4c MATLAB is employed to execute the numerical solutions. Analysis of stability is also reported. Due to the mixed convection parameter, the opposing flow contributes towards two different alternative solutions, but the second solution is not stable. A higher local Nusselt number are achieved by increasing the concentration of magnetic nanofluid up to 2% and enlarging the mixed convection parameter under the influence of the porosity regime in the vertical rotating cone. It has been established in this study that the addition of cobalt ferrite as the magnetic nanoparticles (MNPs) is proven to have the ability in enhancing the thermal performance of the fluid.